Ice age collection [videorecording (Blu-Ray)] - Wedge, Chris, 1958-; Saldanha, Carlos, 1965-; Leary, Denis; Leguizamo, John; Romano, Ray (Twentieth Century Fox Home Entertainment, 2017)
A band of creatures fleeing the coming frost tries to reunite a human baby with its tribe; the Ice Age is coming to an end and Manny, a wooly mammoth, and his friends make their way to a distant part of their valley to escape the oncoming flood waters from the melting glaciers; Manny and his friends discover a lost world of dinosaurs; when he is separated from his family, Manny sets off to find a land bridge to reunite him and his family; when Scrat creates a meteor shower that threatens the Earth, the animals must band together to find a way to keep one giant meteor from destroying the world.